Developing Students’ Reading Comprehension Using Inquiry Method - Indriyani, Muldiyati; Suwandi Suwandi; Ririn Ambarini (Lembaga Pengembangan Kinerja Dosen, 2023)
The main aim of this study was to assess the efficacy of the Inquiry technique in improving reading comprehension skills. This study utilized a quantitative and pre-experimental methodology for the purpose of conducting tests. The pre-experimental design included two evaluations: an initial pre-test and a subsequent post-test carried out following the intervention. The study's sample size comprised 30 students in the eighth grade. The results demonstrated a significant rise in the scores achieved post-test, surpassing the scores achieved pre-test. Furthermore, when the significance level is established at 0.05%, the t-score is considered to be less than the corresponding number in the t-table. The study resulted in the adoption of the Alternative Hypothesis (Ha) and the rejection of the Null Hypothesis (Ho). Hence, it is advisable for educators and students to utilize this method to augment reading comprehension.